OFFLINE INTERNET INNOVATION: NEW OPPORTUNITIES FOR ENTREPRENEURS IN REMOTE DISTRICTS - Yogi Irdes Putra; Irawan, Dodi; Ali Idrus; Subhanadri; Megawati (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
Technological innovation continues to develop, but many remote areas in Indonesia still experience limited internet access. This digital divide has an impact on economic development, especially for local entrepreneurs who rely on technology to grow their businesses. This article examines the potential of offline internet as an innovative solution that enables entrepreneurs in remote areas to overcome internet access constraints, create new opportunities, and drive local economic growth. By utilizing local networks, such as mesh networks and peer-to-peer communication, the offline internet allows entrepreneurs to stay connected, exchange information, and carry out business transactions without having to be directly connected to the internet. This technology provides space for the development of micro, small, and medium enterprises (MSMEs) in remote areas, allowing them to expand markets, accelerate business growth, and increase productivity. This study uses a descriptive qualitative method by conducting a literature review of research articles and books. The results show that offline internet innovation is able to reduce dependence on conventional internet infrastructure, while opening up access to information and markets for entrepreneurs in remote areas. On the other hand, there are still challenges in terms of technology education and the development of adequate local infrastructure to support the adoption of this technology. This article emphasizes the importance of government and private sector support in encouraging the spread of offline internet technology, especially in 3T (Disadvantaged, Frontier, and Outermost) areas. This innovation, if supported by the right policies, has the potential to become a driving force for digital entrepreneurship in remote areas, as well as bridge the digital divide that has been the main obstacle in local economic development.